2013
DOI: 10.1007/s40261-013-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tolerability, and Safety of Intranasal Administration of Reformulated OxyContin® Tablets Compared with Original OxyContin® Tablets in Healthy Adults

Abstract: Background and Objective Reformulated OxyContin Ò (oxycodone-HCl controlled release) tablets (ORF) became available in the United States in August 2010. The original formulation of OxyContin Ò (oxycodone-HCl controlled release) tablets (OC) used a delivery system that did not provide inherent resistance to crushing and dissolving. The objective of this study was to compare the pharmacokinetics, tolerability, and safety of finely crushed ORF tablets, coarsely crushed ORF tablets, and finely crushed OC tablets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…The area under the concentration-time curve (AUC) was approximated using the linear trapezoidal method. The Cmax/Tmax ratio (abuse quotient) served as an index of the average rate of increase in drug concentration from dosing to Tmax (Perrino et al, 2013). (West, Welch, & Galecki, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The area under the concentration-time curve (AUC) was approximated using the linear trapezoidal method. The Cmax/Tmax ratio (abuse quotient) served as an index of the average rate of increase in drug concentration from dosing to Tmax (Perrino et al, 2013). (West, Welch, & Galecki, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The only two published studies that have compared the abuse liability of the original OxyContin® and the reformulated OxyContin® are intranasal studies (Perrino et al, 2013;Harris et al, 2013). In these studies, the participants [with a history of opioid abuse/misuse in Perrino et al (2013) and nonmedical use of opioids in Harris et al (2013)], were asked to snort crushed tablets. Together, the studies showed that the original OxyContin® produced relatively greater positive subjective effects, less negative effects (less nasal discomfort) and had a greater abuse quotient (a shorter Tmax and a greater Cmax) compared to the reformulated product.…”
Section: Controlled-release Oxycodone Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Support for this relationship has been demonstrated in studies of opioids, sedatives, and methylphenidate. [4][5][6][7][8] However, at the individual subject level, PK/PD correlations are often much weaker, suggesting that PK/PD relationships are highly variable and may depend on factors such as formulation or route of administration. 9,10 An extended-release (ER) tablet formulation of hydrocodone (Vantrela R ER; Teva Pharmaceuticals, Inc., Frazer, Pennsylvania) was developed using the CIMA R Abuse-Deterrence Technology platform to provide resistance against the rapid release of hydrocodone when tablets are manipulated or taken with alcohol.…”
mentioning
confidence: 97%
“…This is not the case for the approved OxyContin label, which contains within a boxed warning the statement “Instruct patients to swallow OXYCONTIN tablets whole; crushing, chewing, or dissolving OXYCONTIN tablets can cause rapid release and absorption of a potentially fatal dose of oxycodone” [4]. Both the Gudin et al 2015 data and Purdue’s own data [5], showing that manipulation of OxyContin was able to compromise its ER mechanism, support inclusion of such a statement in the label.…”
mentioning
confidence: 99%